The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2016
DOI: 10.1186/s40064-016-2891-0
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of pharmacological activity of Hibiscus tiliaceus

Abstract: Hibiscus tiliaceus, locally known as Bhola was examined for phytochemical properties and its cytotoxic, antibacterial, analgesic and neuropharmacological activities using the ethanol extract of leaf and bark. The phytochemical analysis of the leaf extract indicated the presence of tannins, whereas bark extract indicated the presence of alkaloid, reducing sugar and tannins. A preliminary cytotoxicity of these extracts was determined by a simple and low cost assay using brine shrimp lethality. The leaf extract o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 14 publications
(13 reference statements)
0
14
0
5
Order By: Relevance
“…Data were analyzed by using One-way ANOVA followed by Duncan's multiple comparison tests prostaglandins (PGs), bradykinins and substance P at the nerve ending [41]. Thus, the analgesic activities of the extract may be presence of saponins and that too pharmacological history of these compounds in analgesic and antispasmodic activity [42]. Moreover, the finding of the present study had shown 8.60% and 32.03% at 200 and 400 mg/kg b.wt.…”
Section: Discussionmentioning
confidence: 99%
“…Data were analyzed by using One-way ANOVA followed by Duncan's multiple comparison tests prostaglandins (PGs), bradykinins and substance P at the nerve ending [41]. Thus, the analgesic activities of the extract may be presence of saponins and that too pharmacological history of these compounds in analgesic and antispasmodic activity [42]. Moreover, the finding of the present study had shown 8.60% and 32.03% at 200 and 400 mg/kg b.wt.…”
Section: Discussionmentioning
confidence: 99%
“…Di Indonesia, tanaman waru mudah ditemukan dan dapat tumbuh di segala macam lingkungan. Oleh masyarakat, selain sebagai tanaman peneduh, umumnya daun waru digunakan sebagai obat tradisional untuk menyembuhkan penyakit demam, batuk, infeksi telinga, sesak nafas, diare, disentri, tipus, TBC, randang amandel, peradangan usus, abses, penyubur rambut dan bisul [3,4,5]. Berbagai macam khasiat daun waru ini disebabkan adanya kandungan senyawa kimia yang terkandung di dalamnya, seperti flavonoid, tannin, polifenol, saponin, alkaloid dan steroid [6,7,8].…”
Section: Pendahuluanunclassified
“…Alkaloid juga bertindak sebagai senyawa antikanker [15]. Alkaloid dan saponin memiliki efek farmakologis yaitu analgesik (pereda nyeri), antispasmodik (pereda kram pada perut), dan pengobatan artritis (radang persendian) [3].…”
Section: Hasil Dan Pembahasanunclassified
“…Hibiscus tiliaceus; chloroplast genome; phylogenetic analysis Hibiscus tiliaceus L. (Malvaceae) is a common coastal semimangrove plant that is widely distributed in tropical and subtropical America, Africa, Asia, Australia, and throughout the Pacific islands (Abdul-Awal et al 2016). As a fast-growing, wind-and salt-resistant tree or larger shrub, it grows well and is abundant in littoral forests and mangrove forest margins of atolls and high islands (Feng et al 2008).…”
mentioning
confidence: 99%
“…It was used for the stabilization of sand dunes, the formation of coastal windbreaks, and also as a landscape tree species inland due to its wide adaptation various eco-geographic conditions (Tang et al 2003). In addition, it has been used as a traditional medicine for the treatment of fevers and coughs, ear infections and abscesses, postpartum disorders, and skin diseases in Asian and African countries (Vanzella et al 2012;Abdul-Awal et al 2016). The phylogeography and genetic diversity of H. tiliaceus have been assessed on the basis of variations in chloroplast (cp) DNA sequences in several previous studies (Tang et al 2003;Takayama et al 2006;Yang et al 2011;Shi et al 2020).…”
mentioning
confidence: 99%